Can Mentimeter Become an Innovative Media in Sharf Learning? - Faizmailiatus Sofa; Zainal Arifin Ahmad; Nasiruddin; Syiva Nurul Afifah (STUDI ARAB, 2022)
The main objective of this research is to describe whether Mentimeter can be an innovative solution environment applied to Sharaf learning which is caused by the unenthusiasm and inactivity of students in Sharf learning in the Arabic Language Education study program at UIN Sunan Kalijaga. The study was conducted in a qualitative descriptive manner and its subject was Sharf's learning. This technique gathering data for this research in the form of documents, interviews, and observations. And the analysis technique uses presentation, condensation, and inference of data. Mentimeter is capable and capable of being an innovative medium for learning Sharf. With Mentimeter, it will raise student attention so that students will focus during learning. This can increase student enthusiasm for learning, making them carry out teaching and learning activities to the fullest. However, due to limited time, the use of multimeters in Sharf learning has not been able to run optimally and not all students have answered the questions posed in Mentimeter.